Multilevel analysis of intimate partner violence and associated factors among pregnant women in East Africa: Evidence from recent (2012-2018) demographic and health surveys - Desale Bihonegn Asmamaw; Wubshet Debebe Negash; Desalegn Anmut Bitew; Tadele Biresaw Belachew (BMC, 2023)
Abstract Background Globally, intimate partner violence (IPV) during pregnancy is the most common and major public health problem. It has a negative effect on the lives of both mother and fetus. Despite its prominence, many countries in East Africa have paid little attention to this issue. This study assessed the prevalence and associated factors of intimate partner violence among pregnant women in East African countries. Methods The study adopted a secondary method data analysis that utilized recent Demographic and Health Surveys of 10 countries in East Africa between 2012 and 2018. A total of 23,521 women who gave birth in the 5 years preceding the survey were included. A multilevel mixed-effect logistic regression model was fitted to identify factors associated with IPV. Variables with a p-value < 0.05 were declared as significant factors associated with IPV. Results The overall prevalence of IPV in East Africa was 37.14 (95% CI 36.53, 37.76). Women with age 25-34 (AOR = 1.20;95%CI; 1.06, 1.36), 35-39 (AOR = 1.40;95%CI; 1.24, 1.58), and 40-49 (AOR = 1.66;95%CI; 1.43, 1.95), women with no education (AOR = 1.27;95%CI; 1.16, 1.39), women with no occupation (AOR = 1.36; 95%CI; 1.27, 1.47), women from households with the poorest (AOR = 1.51; 95%CI: 1.33, 1.71), poorer (AOR = 1.40;95% CI:1.24, 1.58), middle (AOR = 1.32;95%CI:1.17, 1.48), and richer (AOR = 1.26;95%CI: 1.13, 1.40), husband drinks alcohol (AOR = 2.54; 95%CI 2.39, 2.71), ≥ 5 number of living children (AOR = 1.28; 95%CI: 1.31, 2.57) and rural areas (AOR = 1.14; 95%CI: 1.03, 1.25) were significantly associated with IPV. Conclusion More than one-third of pregnant women experienced intimate partner violence in East Africa. Promoting the educational status of women, the economic capacity of women, and the healthy behavior of the husband by reducing alcohol consumption, with particular attention to rural women and violence during pregnancy, is vital to reduce the prevalence of IPV.